Hidden texts, hidden nation : (re)discoveries of Wales in travel writing in French and German (1780-2018) - Jones, Kathryn N.; Tully, Carol Lisa; Williams, Heather, 1972- (Liverpool University Press, 2020)
This book offers a fresh and timely 'European' perspective on Wales and Welshness. Uncovering rare travel texts in French and German from 1780 to now it provides a valuable case-study of a culture that is often minoritized, and demonstrates the value of multilingual research and a transnational approach.